Typical angina during exercise stress testing improves the prediction of future acute coronary syndrome. (25th February 2021) - Lindow, Thomas; Ekström, Magnus; Brudin, Lars; Carlén, Anna; Elmberg, Viktor; Hedman, Kristofer
Abstract: Introduction: The prognostic value of angina during exercise stress testing is controversial, possibly due to previous studies not differentiating typical from non‐typical angina. We aimed to assess the prognostic value of typical angina alone, or in combination with ST depression, during exercise stress testing for predicting cardiovascular events. Methods: We conducted a prospective observational cohort study including all patients who performed a clinical exercise stress test at the department of Clinical Physiology, Kalmar County Hospital between 2005 and 2012. The association between typical angina/ST depression and incident acute coronary syndrome (ACS) and cardiovascular mortality were analysed using Cox regression for long‐term and 1‐year follow‐up. Results: Out of 11605 patients (median follow‐up 6.7 years), 623 (5.4%) developed ACS and 319 (2.7%) died from cardiovascular causes. Compared to patients with no angina and no ST depression, typical angina and ST depression were associated with increased risk of future ACS; hazard ratio (HR) 3.5 ([95%CI] 2.6–4.7). This association was even stronger for ACS within one year (typical angina with and without concomitant ST depression; HR 20.8 (13.9–31.3) and 9.7 (6.1–15.4), respectively). Concordance statistics for ST depression in predicting ACS during long‐term follow‐up was 0.58 (0.56–0.60) and 0.69 (0.65–0.73) for ACS within one year, and 0.64 (0.62–0.66) and 0.77 (0.73–0.81), respectively, when typical angina was added to the model. Conclusions: Typical angina during exercise stress testing is predictive of future ACS, especially in combination with ST depression, and during the first year after the test.